Yinzhihuang oral liquid in the treatment of neonatal jaundice: a meta-analysis - Jie Zeng; Su-jun Wang; Yong-mei Li; Hang-shan Li; Qian Luo; Yun-ying Huang; Qun Jiang; Li Wang (Taylor & Francis Group, 2017)
Context: Yinzhihuang oral liquid, a well-known Chinese herbal formula, is a clinical drug for the treatment of neonatal jaundice, and a number of clinical trials have been published addressing this issue, but there is no comprehensive analysis that evaluates its efficacy for the treatment of newborn with hyperbilirubinaemia. Objective: A meta-analysis was conducted to evaluate the efficacy of Yinzhihuang oral liquid on neonatal jaundice. Methods: Search was performed throughout PubMed, Cochrane Library, EMBASE, Ovid, Wanfang, VIP Medicine Information System (VMIS) and China National Knowledge Infrastructure (CNKI) databases up to December 2015. The search terms were (Yinzhihuang oral liquid or Yinzhihuang oral solution), (neonatal jaundice or neonatal hyperbilirubinaemia), and (efficacy). Review Manager 5.2 software was used for analyzing the data. Data were pooled by using the random-effects models and expressed as relative ratio (RR), standardized mean difference (SMD) or mean difference (MD) with a 95% confidence interval (CI). The Cochrane tool was applied to assess the risk of bias of the trials. Results: Yinzhihuang oral liquid in conjunction with other therapy increased effective rate of neonatal jaundice therapy (RR =1.14, 95%CI: 1.08-1.20). Yinzhihuang oral liquid significantly eliminated overproduced bilirubin which was measured by TSB or TCB at the third day and fifth day during the treatment {[third day, SMD = −1.63, 95%CI: −2.20 to (−1.06)], [fifth day, SMD = −5.00, 95%CI: −7.88 to (−2.12)]}; Yinzhihuang oral liquid significantly shortened jaundice subsiding time [MD = −3.20, 95%CI: −6.01to (−0.39)]. Conclusion: Yinzhihuang oral liquid can be considered as an effective treatment option for neonatal jaundice.